Fungal species composition and load of indoor air in a school cafeteria - Tinampay, Arvin Jay
Students spend a lot of time inside classrooms and cafeterias without knowing the potential hazards when they are exposed to indoor air pollutants (i.e., chemical and biological agents). In more developed countries, the concern for the so-called ?sick building syndrome? has already gained general acceptability and recognition. As such, a certain level of air quality must be maintained in closed environments to prevent allergies and disease development associated with chemical and microbial exposure. Among the microbes, fungi are ubiquitous and prolonged exposure and inhalation of their spores can cause serious health problems in the future. Recent studies have found links between epidemiological allergies and exposure to airborne fungi. Unfortunately, little or no attention has been given locally to address the issue. Therefore, as a primary step to establish a benchmark data, this study was conducted to isolate and identify fungal species present and the fungal load within a school cafeteria and to compare those found outside of the building. This study used the settle plate method (with three replicates) to sample fungi at the folling sites: Site 1 (entrance), Site 2 (water dispenser area), Site 3 (Main dish counter), Site 4 (snack counter), Site 5 (center table); the outdoor environment was sampled just outside the main entrance. Sampling was done only once in April 2018. Results showed an arithmetic mean of 13 CFU/plate for indoor environment while outdoor environment had a higher mean at 37 CFU/plate but nor statistically different (p<0.05). On the other hand, among the 15 plates exposed at various locations indoors, location 2 (water dispenser area) recorded the highest mean fungal load at 27.3 CFU/m3. Comparison of fungal load between indoor and outdoor environments showed a higher load outside than indoor at 19 CFU/m3 and 53 CFU/m3, respectively and the result is statistically significant (p<0.002). In general, the indoor fungal load is categorized as good based on the Index of Microbial Contamination (IMA) while the outdoor environment falls into the poor category. The fungi isolated from the settle plates were mostly allergenic and toxic species such as Aspergillus niger and Aspergillus flavus. The initial results of this study would be useful as baseline for more detailed monitoring in the future load and species composition in the cafeteria.